(untitled) (INNOVATIVE ECONOMY, 2020)
Hubeni Yu.E. ECONOMIC SECURITY OF AGRICULTURAL ENTERPRISES: DETERMINATION OF BEHAVIORAL FACTORS OF LAND RELATIONS Purpose. To investigate the influence of human motivation and behavioral factors (estimation, expectations, motives for making decisions, etc.) in land relations on the economic security of agricultural enterprises. Methodology of research. The article is prepared on the basis of empiric data, formed while making 4 applied research projects during 2016 - 2018 (basic project – 1996). The projects were made in Lviv villages (Ukraine). They were independent, had agreed methods and approximate structure. Sociological polls are the basis of the projects. The projects were aimed at performing activities similar methodologically. The method of sociological survey, including personal questionnaires, comparisons, retrospective analysis and data reduction, was used. Findings. It was found that structural and habitual transformations in the village. Considerably change the motives, rational expectations and induced factors of decision-making concerning farming by land-owners. Market relations urged them to extending pragmatism and rationalism. Motivation change of land-owners’ behavior influences considerably economic security of agricultural enterprises. We substantiated the necessity of intensifying public communication of tenant farmers and landholders, enterprises and other agricultural producers and rural communities. Economic circumstances will urge to intensify cooperation and coordination of land-owners and landholders. Agricultural enterprises also have to increase cooperative social responsibility. Originality. The role and importance of behavioral component of land relations and its influence on economic security of agricultural enterprises are substantiated. It is determined, that a rather large group of characteristics of land relations (stability of land tenure, conditions of land lease and corresponding rental payment, farming image) directly depends on evaluation and economic expectation of rural population. The specific role of non-material factors (trust, traditions, decency, stability, etc.) in lease relations is determined. Practical value. The results of the research are of practical importance for forming land policy of agricultural enterprises, aimed at increasing economic security and stability. Key words: economic security; agricultural enterprises; land relations; behavioral factors; rural population; land lease